Effect of epichloid endophytes and soil fertilization on arbuscular mycorrhizal colonization of a wild grass - Vignale, Maria Victoria; Iannone, Leopoldo Javier; Pinget, Albertina Daniela; De Battista, Jose Pedro; Novas, María Victoria (2018)
Background and aims: Plants often establish multiple simultaneous symbiotic associations with different micro-organisms; however, the way in which each symbiont affects the other symbionts and the effects of these multiple interactions on plant performance are not well understood. The aim of this study was to evaluate how two different asexual Epichloë species modulate the establishment of arbuscular mycorrhizal fungi (AMF) in a wild forage grass under different soil fertilization levels. Methods: We performed a completely randomized 12-month-long field experiment to evaluate the effect of two B. auleticus-endophyte ecotypes and two soil fertilization levels on the colonization of AMF, in seedlings and adult plants. Plant biomass and reproductive tillers production were also measured. Results: The symbiosis, measured as the total extent of AM fungal colonization and frequency of arbuscules was significantly higher in Epichloë-infected plants and was not affected by fertilization either in seedlings or in adult plants. Plant biomass was increased by fertilization but no differences were observed due to the endophytic status. However, E+ plants produced more panicles than their E− counterparts. Conclusions: Our findings strongly support the hypothesis of positive association between Epichloë endophytes and AMF in wild grasses, making this model important for agronomic improvement.